Rural-urban transformation in Uganda - Mukwaya, Paul; Bamutaze, Yazidhi; Mugarura, Samuel; Benson, Todd (International Food Policy Research Institute, 2012)
Uganda over the last twenty years has maintained high economic growth rates, increasing urbanization and shifting pat-terns in sectoral contribution to overall development. An increasing proportion of the wealth generated by Uganda’s economy is shifting from being a product of agricultural activities to coming out of the service sector of the economy, in particular. However, this shift in the sources of wealth in the economy is not being accompanied by a shift in employment out of agriculture to the other sectors. Rather, what we find is that employment is actually increasing in agriculture, even as its contribution to Uganda’s economy is declining. The increasing number of Ugandans engaged in agriculture is more a reflection of the inability of the more modern sectors of the economy to provide adequate employment for the many Ugan-dans entering the workforce every year.